Time in and for nature-based solutions. No quick fix solutions for complex ecological and social processes - Ina Lehmann; Julia Grosinger; Steffen Bauer; Jean Carlo Rodríguez de Francisco; Katarzyna Negacz; Jonas Hein (Nature-Based Solutions)
Nature-based solutions (NbS) are an increasingly widespread tool in environment and development policies. They embody the idea that nature and natural processes can be purposefully used by humans to provide solutions to pressing environmental and social challenges. However, their potential to meet this ambition is contested, particularly in terms of the scale of the challenge, the risk of diverting attention from the need for decarbonisation, and examples of poorly implemented NbS projects. A largely overlooked but crucial factor concerning the effectiveness of NbS is time. In response to this gap, we develop a framework for systematising the ecological and social dimensions of time in NbS as well as the distinction between slow and fast processes. On this basis, we gather insights from a systematic literature review on key challenges related to slow and fast processes in both the ecological and social dimensions of time. For instance, the long maturation time of many species and ecosystems may be incompatible with the often short-term logic of NbS projects or with the dynamic character of ecosystems that may be challenging for continuous benefit provision. We also identify practical recommendations from the literature review for incorporating time into NbS design, for instance through adaptive monitoring, and we conclude with an urgent call for a more long-term perspective for NbS policies and practice.